Adoption of Integrated Food-Energy Systems: Improved Cookstoves and Pigeonpea in Southern Malawi - Orr, Alistair; Kambombo, Blessings; Roth, Christopher; Harris, Dave; Doyle, Vincent (Cambridge University Press, 2015)
We analyse the adoption of an Integrated Food-Energy System (IFES) in southern Malawi. The IFES combined the improved cookstove (chitetezo mbaula in Chichewa), designed to reduce demand for fuelwood, with the pigeonpea variety Mthawajuni, which increased both food supply and supply of fuelwood from pigeonpea stems. Adoption of the improved cookstove was found to be higher among households that were better off and where women had greater control over decision-making. However, adoption of the IFES was not associated with reduced demand for fuelwood from forests and hills or reduced frequency of collection. IFES adopters might have high fuelwood consumption because they were better off, but fuelwood consumption in better-off households did not differ significantly between IFES adopters and non-adopters. Pigeonpea increased food supply for adopter households, including children aged less than five years. Consequently, the IFES has had mixed results, improving food supply but not reducing demand for fuelwood. Households ranked early maturity, fuelwood and yield as the three most important reasons for preferring Mthawajuni over other varieties of pigeonpea. The plant breeding programme for pigeonpea in Malawi should evaluate improved varieties not only for earliness and grain yield but also for the production of fuelwood. Improved varieties with desirable market traits have had limited success in the absence of reliable markets and price incentives.